Molecular Mechanisms of Trophoblast Dysfunction Mediated by Imbalance between STOX1 Isoforms - Aurélien Ducat; Betty Couderc; Anthony Bouter; Louise Biquard; Rajaa Aouache; Bruno Passet; Ludivine Doridot; Marie-Benoîte Cohen; Pascale Ribaux; Clara Apicella; Irène Gaillard; Sophia Palfray; et al. (iScience, 2020)
Summary: STOX1 is a transcription factor involved in preeclampsia and Alzheimer disease. We show that the knock-down of the gene induces rather mild effect on gene expression in trophoblast cell lines (BeWo). We identified binding sites of STOX1 shared by the two major isoforms, STOX1A and STOX1B. Profiling gene expression of cells overexpressing either STOX1A or STOX1B, we identified genes downregulated by both isoforms, with a STOX1 binding site in their promoters. Among those, STOX1-induced Annexin A1 downregulation led to abolished membrane repair in BeWo cells. By contrast, overexpression of STOX1A or B has opposite effects on trophoblast fusion (acceleration and inhibition, respectively) accompanied by syncytin genes deregulation. Also, STOX1A overexpression led to abnormal regulation of oxidative and nitrosative stress. In sum, our work shows that STOX1 isoform imbalance is a cause of gene expression deregulation in the trophoblast, possibly leading to placental dysfunction and preeclampsia.